A new type of congenital hepatic hemangioma - rapid postnatal proliferation followed by regression - Yang, Luyao; Dou, Weitao; Chen, Xin; Teng, Jianbo; Wei, Xinhong (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to analyze and summarize the prenatal and postnatal imaging findings, as well as the postnatal growth curves, of patients with hepatic hemangiomas (HHs) that were identified in utero and continued to proliferate after birth.MethodsA retrospective study was conducted to collect and analyze data from children with congenital hepatic hemangiomas (CHH) who were diagnosed and followed-up at our hospital between January 1, 2016 and December 30, 2023. These children exhibited rapid postnatal proliferation of lesions, followed by spontaneous regression. The study recorded the patients’ general clinical information, laboratory test results, and pre- and postnatal imaging characteristics of the tumor, as well as changes in tumor volume over time.ResultsEight patients (four males and four females) were included in this group, with and average gestational age of 37 weeks at the initial onset. The imaging features of this type of hepatic hemangioma are almost indistinguishable from those previously described for CHH. The only difference was that 87.5% of the tumors were located in the left lobe of the liver, and no calcification was observed within the tumors during the prenatal and proliferative stages. The postnatal growth trend of the tumors was very rapid, with complete proliferation occurring within the first six months after birth (median, 66 days) and the peak volume exceeding 1.5 × the initial volume. Of the tumors, 87.5% (7/8) regressed to 80% of the initial volume within one year, and the median time to complete regression was 365 days (range 300-730). None of the patients experienced adverse symptoms or complications during the study period.ConclusionsThis article describes a special type of CHH that can continue to proliferate after birth. However, the tumor spontaneously regresses over time without complications. Therefore, for postnatal CHH growth, regular imaging observation without drug treatment or surgery is recommended, thereby preventing overtreatment while ensuring normal child development.